Analyse économique des instruments indirects de la politique monétaire de la zone euro: Economic analysis of indirect instruments of monetary policy in the euro area - Nacer-Eddine MOUFFOK; Madjid OUTMEZAB (Journal of North African Economies, 2025)
The purpose of this article is to present an economic analysis of the indirect instruments of monetary policy of the European Central Bank (ECB) from 1999 to date. Thus, we carried out a study of the indirect instruments of the common monetary policy, based on a qualitative and quantitative analysis of the data extracted from the various official sites of this institution. The first results show that the effects of monetary policy on inflation, the main objective of the ECB, and on the economy only materialize after a certain period, because these effects follow several transmission channels which are slow. , complex and different from one State to another within the euro zone itself, which makes decisions on single currency policy difficult, especially after the last financial crisis.